The image of old age in selected cultural texts – an analysis of middle school textbooks for Polish classes - Kalinowska, Monika Anna (Instytut Socjologii Uniwersytet Wrocławski, 2014)
The presented text concerns the image of old age in middle school textbooks for literary and cultural education. It is separated into three areas of description: physical, mental, and spiritual.
Keywords: old age; textbook; middle school; cultural texts